SPOILAGE OF PRAWNS AT 0* C. AND ITS ASSESSMENT BY CHEMICAL AND BACTERIOLOGICAL TESTS - Velankar, N K; Govindan, T K; Appukkuttan, P N; Iyer, K Mahadeva (Indian Journal of Fisheries, 2011)
STUDIES on the spoilage of iced prawns and its assessment by objective testswere reported earlier (Velankar and Govindan, 1959). These studies revealedthat considerable losses of ’ extractives’ such as the free amino-acids occurduring storage of prawns in ice due to leaching. Work done in the U.S.A.(Collins et al, 1960) and in India (J. R. Iyengar et al, 1960) has also shownthat water-soluble chemical compounds including those produced throughspoilage leach out during storage in ice. In order to evaluate accurately thedevelopment of the spoilage products it is necessary to carry out the investigationson prawns held at 0Â° C, i.e., the melting point of ice, without contactwith ice. The results of these studies carried out by us are reported in thepresent paper.